PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN DAN LEMBAR KERJA PESERTA DIDIK MENGGUNAKAN PEMBELAJARAN PROBLEM-BASEDDALAM PENGAJARAN TEKS ANALYTICALEKSPOSISI PADA PESERTA DIDIK TAHUN KEDUA DI SMA - Ulfa, Nurul; Pratiwi, Atni; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aimed to develop English instructional tools consist of Lesson Plan and Students' Worksheet, also to find out the validity level of the Instructional tools that were developed by applying Problem-Based Learning as one of the learning methods suggested in the 2013 curriculum. These two Instructional tools were designed to teach Analytical Exposition texts for the second year students of SMA. This research is a developmental research using 4-D Model which conducted only until the 3rd stage; (a) define stage is done to collect various information relating to the product that was developed, (b) design stage is done to plan the draft of instructional tools and arranged it into the right format and (c) develop stage which is done to validate and try-out the instructional tools to the real target. While the last stage of the 4-D Model, namely Disseminate, wasn't conducted due to specific reasons. To find out the validity level of Instructional Tools, the data were collected using the validation sheet of Lesson Plan, validation sheet of Students' Worksheet, which assessed by validators, and students' response questionnaires. Based on the data analysis result, the validation score of the Lesson Plan, Students' Worksheet, and the average score of students' responses are categorized as very valid Instructional Tools, which means that they are ready to be implemented to the second year students of SMA.Key Words: Developing, Lesson Plan, Students? Worksheet, Problem-Based Learning (PBL) , Analytical Exposition Texts.